Physical Activity, the Childhood Cancer Symptom Cluster–Leukemia, and Cognitive Function: A Longitudinal Mediation Analysis. Issue 6 (November 2018) - Hooke, Mary C.; Rodgers, Cheryl; Taylor, Olga; Koerner, Kari M.; Mitby, Pauline; Moore, Ida; Scheurer, Michael E.; Hockenberry, Marilyn J.; Pan, Wei
Abstract : Background: Children undergoing leukemia treatment report co-occurring symptoms of fatigue, sleep disturbances, pain, nausea, and depression as a symptom cluster. Physical activity (PA) is essential for development and may influence symptom severity. Children with leukemia are at risk of cognitive impairments from central nervous system therapies. Using a longitudinal parallel-process model, relationships among function and symptom clusters were explored. Objective: This study examined the longitudinal mediation effects of PA on cognition via a symptom cluster during leukemia treatment. Methods: Symptoms, PA, and cognitive function of 327 children aged 3 to 18 years were measured over 4 intervals during the first year of leukemia treatment. Children 7 years or older self-reported and parents reported for younger children. Parents completed cognitive function measurements for all children. The influence of the first time point and the subsequent change between all 4 time points of PA on the symptom cluster were explored. Analysis determined whether the symptom cluster mediated the effect of cognition over the treatment period. Results: Patients with a higher PA at time 1 reduced their symptom cluster severity over the measurements. However, when PA increased over the measurements, symptom cluster severity also increased. When the symptom cluster was more severe at time 1, cognitive function was lower at time 1, and cognitive function decreased over time. When symptoms became more severe over time, cognitive function declined. Conclusions: The symptom cluster acted as a mediator between PA and cognition. Implications for Practice: Symptom management during treatment may be an additional strategy for protecting cognitive function.